2014
DOI: 10.1158/1535-7163.mct-13-0963
|View full text |Cite
|
Sign up to set email alerts
|

Selective Activity of the Histone Deacetylase Inhibitor AR-42 against Leukemia Stem Cells: A Novel Potential Strategy in Acute Myelogenous Leukemia

Abstract: Most patients with acute myelogenous leukemia (AML) relapse and die of their disease. Increasing evidence indicates that AML relapse is driven by the inability to eradicate leukemia stem cells (LSC). Thus, it is imperative to identify novel therapies that can ablate LSCs. Using an in silico gene expression-based screen for compounds evoking transcriptional effects similar to the previously described anti-LSC agent parthenolide, we identified AR-42 (OSU-HDAC42), a novel histone deacetylase inhibitor that is str… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 46 publications
2
41
0
Order By: Relevance
“…In addition to proteasome inhibitors like MG-132, other compounds with inhibitory activity against NF-κB including parthenolide (PTL) [49], AR-42 [50], and niclosamide [51] have also be reported to target primitive AML cells. PTL is the major active compound in the herbal medicine Feverfew ( Tanacetum parthenium ) and is one of the first compounds shown to selectively ablate LSCs without significant toxicity to normal HSPCs [49, 52].…”
Section: Inhibition Of Nuclear Factor (Nf)-κbmentioning
confidence: 99%
“…In addition to proteasome inhibitors like MG-132, other compounds with inhibitory activity against NF-κB including parthenolide (PTL) [49], AR-42 [50], and niclosamide [51] have also be reported to target primitive AML cells. PTL is the major active compound in the herbal medicine Feverfew ( Tanacetum parthenium ) and is one of the first compounds shown to selectively ablate LSCs without significant toxicity to normal HSPCs [49, 52].…”
Section: Inhibition Of Nuclear Factor (Nf)-κbmentioning
confidence: 99%
“…At sub mM concentrations, this novel HDAC inhibitor was shown to exert anti-proliferative and cytotoxic activities against lymphocytic/acute myeloid leukemia cells, and B-cell lymphoma cells [9e12]. Studies have also shown that AR-42 could directly target leukemic stem cells [10]. However, the potential activity of AR-42 in colon cancer cells is not extensively studied, and the underling mechanisms need further characterizations.…”
Section: Introductionmentioning
confidence: 99%
“…Total p65 protein levels remained unchanged after treatment, while phospho‐p65 levels diminished with PTL treatments in both CML cell lines and in a primitive population from a CML patient, indicating an inhibition of the NF‐κB canonical pathway (Figure 5B). Furthermore, to verify the functional status of NF‐κB, transcriptional activity of the pathway was evaluated in CML cell lines (K562, Meg‐01, KCL‐22, Kasumi‐4), AML cell line HL60 and primary CD34 + lin − cells from CML and NBM samples, according to Guzman and collaborators 22. Cells were cultured for 6 hours in the absence or presence of PTL or DMAPT at 7.5 μmol/L.…”
Section: Resultsmentioning
confidence: 99%